Commodities Price Pass-Through in Costa Rica, Does the Level of Competition influence? - Álvarez Corrales, Cristian (2018)
We study the presence of asymmetries in the pass-through of commodities prices to domestic prices in Costa Rica by means of structural distributed lags models to deal with the asymptotic bias that emerges when censored VAR models (the traditional approach) are employed to capture asymmetries. The pass-through to consumer price index does not show evidence of asymmetry, but in products associated with wheat, maize, rice and fertilizers the pass-through is asymmetric. We also found that the asymmetry becomes higher as the concentration of suppliers increases.